The correlation between basic measles immunization historical and nutritional status on toddler: factorial stunting prevalence - Bella Mardya; Muhsinin, Muhsinin; Diah Retno Wulan (Jurnal Keperawatan, 2023)
Introduction: The problem of nutritional status on toddlers is still one of the world’s problems that must continue to be resolved, such as stunting. Stunting, or being too short for one’s age, is defined as below -2 standard deviations from the median height-for-age z-score. Stunting can directly be affected by infectious disease and incomplete immunization such as basic measles immunization. Objectives: This research aims to determine and analyze the correlation between giving basic measles immunization and nutritional status, especially the incidence of stunting on toddlers. Methods: This research was an observational analytic study using a cross-sectional approach with non-probability sampling. The samples were 134 toddlers who were 12-36 months, were not sick, and have the KIA/KMS book. Basic measles immunization and nutritional status were dependent variables whereas stunting prevalence was an independent variable. Data analysis used the Spearman’s Rho correlation test with α = 0.05. Results: The results showed the majority of toddlers experienced nutritional status problems especially stunting (51.5%) and the majority of toddlers had received basic measles immunization (67.9%). Based on the Spearman’s Rho statistical test, obtained p-value = 0.003 (p-value < 0.05) with correlation coefficient (r) = -0.251. Conclusions: There is a significant correlation between basic measles immunization and nutritional status, especially in the incidence of stunting. This finding suggests that the local government should initiate an innovative program of health education focusing on knowledge and prevent the increasing stunting such as by collaborating with the nursing profession which can act as a good educator and caregiver.